Role Of Indonesian Cancer Foundation In Early Detection Program - LUWIA, MELLISA S (Indonesian Journal of Cancer, 2010)
https://www.scribd.com/doc/43614860/Role-Of-Indonesian-Cancer-Foundation-In-Early-Detection-Program